Study on U hull modifications with concave design to improve the tourist ship stability - Syahril Syahril; Rahmat Azis Nabawi; Aulia Zulkarnaen Nasty (Journal of Engineering Researcher and Lecturer, 2023)
Stability is an important aspect that was studied in ship design as it relates to the safety of the ship when facing ocean waves. The tourist ship needed to have a good image in order to attract tourists to use its services. Good stability of the tourist ship was crucial in enhancing the image of the ship and attracting tourists to utilize its services. This research aimed to investigate the effect of concave on the U hull to improve ship stability. The study compared the stability test results of two hull designs: U hull with concave and without concave. The stability tests of both ship models were conducted through simulation methods. The simulations were performed under two conditions: when the tourist ship was empty and when it was fully loaded with passengers. The simulation results indicated that the design of the U hull with concave had a positive influence on ship stability, leading to improved stability. The concave design enhanced the ship's ability to return to its original position when encountering waves. Even in the presence of small waves, the tourist ship did not experience instability.